Investigation on a Duct Noise Control Method through Membranes in Tandem - Cheng Shen; Shasha Yang; Harris K. H. Fan; Randolph C. K. Leung (Shock and Vibration)
Duct noise control is an important practical problem. This paper explores the vibro-acoustic mechanism of duct noise through the membrane in tandem. Validity and feasibility of the proposed analytical model is demonstrated by comparing existing simplified models and full direct aeroacoustic simulation solved with the CE/SE model. It is shown that the coupling effect between two membranes in tandem is not negligible to predict system response. Moreover, introduction of multimembranes is important or even the only efficient way to apply this passive control method in practice.